Grievance Redress Mechanisms in the Health Sector in Mozambique - POTENCIAR (POTENCIAR, 2023)
Context: This research stemmed from learning and changes that occurred in the intervention strategy and budget of the POTENCIAR programme. In consultations and meetings between the Programme Management Unit (UGP) and various actors operating in this area, POTENCIAR’s partners identified — in a participatory and inclusive manner — the issue of grievance redress mechanisms as a problem that they can intervene on within the context of Pro-Accountability Initiatives (PAIs). Taking this perspective , POTENCIAR conceived the present research on mechanisms for complaining about and denouncing poor standards in maternity services. Objectives: The objective of this study was to understand the complaints and grievances management system available to users in the health sector. The insights gained from this study will subsequently feed back into revision s to POTENCIAR’s theory of change and theory of action. The research included mapping the flow of the complaint channel ling process; identifying the motives, capacities, and opportunities for the health authorities to implement the system of mechanisms for redressing complaints; an analysis of how the perspectives of users are perceived, considered, and rejected by health authorities; and, finally, an analysis of the extent to which existing grievance mechanisms are used, including the opportunities, capacities, and motivations for using them.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; governance / governação; health / saúde; mecanismos de reclamação / grievance redress mechanisms

Against the Odds: Action for Empowerment and Accountability in Challenging Contexts - Anderson, Colin; Gaventa, John; Edwards, Jenny; Joshi, Anuradha; Nampoothiri, Niranjan; Wilson, Emilie (Institute of Development Studies, 2022)
How and under what conditions does citizen-led social and political action contribute to empowerment and accountability? What are the strategies used, and with what outcomes, especially in settings which are democratically weak, politically fragile and affected by legacies of violence and conflict? The A4EA programme has explored these questions in Mozambique, Myanmar, Nigeria and Pakistan over five years between 2016-2021. This paper presents the key findings and policy and practice implications from this research across the themes of space for citizen action; citizen-governance relations; women’s political participation and collective action; citizen-led strategies for empowerment and accountability; and enabling citizen action. It also shares important lessons drawn from A4EA experience on conducting and communicating research in complex political contexts like these, and for research consortia. Whilst the research conclusions are drawn from A4EA’s four focus countries, in an increasingly fragile and authoritarian world, the findings are becoming pertinent for more and more contexts across the globe.
Accepted: 2022-02-22T14:59:50Z
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; civic space / espaço cívico; civil society / sociedade civil; conflict / conflito; governance / governação; mobilization / mobilização

Jovens de Gaza defendem que novo instrumento deve desburocratizar a obtenção de DUAT e combater a expropriação de terras pelas elites - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Falando em representação da Governadora da Província de Gaza, a Directora Provincial de Cultura e Turismo denunciou o velho problema de usurpação e acumulação de terra para fins de especulação latifundiária. Trata-se de uma prática comum em Moçambique em que as elites económicas e políticas se apropriam de terras valiosas e ficam à espera do melhor momento para fazer a transacção, preferencialmente com o capital estrangeiro. A representante da Governadora de Gaza disse que esta prática prejudica mais as mulheres que vivem nas zonas rurais por constituírem o grupo que mais usa a terra para a actividade agrícola. A Directora Provincial de Cultura e Turismo em Gaza saudou a iniciativa do CDD de auscultar a juventude sobre a revisão da Política Nacional de Terras, defendendo que, sendo a maioria da população, os jovens devem se apropriar do debate para influenciar a concepção de futuros instrumentos políticos e legais sobre o uso de terras.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; GP - Gaza; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra; youth / juventude

Jovens de Inhambane defendem que futura legislação deve estabelecer um prazo de até 15 dias para resposta ao pedido do DUAT - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Depois da cerimónia inaugural de quinta-feira na Província de Gaza, ontem, sexta-feira, 07 de Maio, foi a vez de Inhambane acolher o debate público no âmbito da auscultação de jovens sobre a revisão da Política Nacional de Terras. Falando na abertura da cerimónia, o Director dos Serviços Provinciais do Ambiente, em representação da Secretária de Estado da Província de Inhambane, defendeu que um dos desafios que a Inhambane enfrenta é o aumento do número de população perante um recurso terra que não é renovável, aliado aos desafios decorrentes das mudanças climáticas que demandam uma compensação da biodiversidade. O Director dos Serviços Provinciais do Ambiente de Inhambane falou também da emergência dos megaprojectos que, para o seu desenvolvimento, precisam do recurso terra. “A iniciativa do CDD de auscultar jovens sobre a revisão da Política Nacional de Terras constitui uma exaltação da cidadania. Todos nós, como moçambicanos, nas nossas comunidades, organizações, temos esta ímpar oportunidade de participar no melhoramento da nossa política de terras”.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; GP - Inhambane; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra; youth / juventude

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Colateralização dos títulos de terra em Moçambique: bases para sua viabilização - Hamela, Hipólito; Macaringue, João; Rose, Ian (USAID, 2021)
No âmbito do processo de Revisão da Política Nacional de Terras e para responder aos consensus alcançados na IX Sessão do Forum de Consulta sobre as Terras (FCT) que incluiam a viabilização da transmissibilidade dos títulos de uso e aproveitamento da terra (DUAT) tornando este processo mais flexível, foi encomendado o presente estudo que tem como objectivo aferir, dentro do actual quadro legal, a viabilidade, sob o ponto de vista de oferta e da procura, da possibilidade de se implementar um programa de empréstimos, oferecendo como garantia, o DUAT. Do estudo resultará um ensaio piloto para testar os pressupostos que o estudo adopta como base, e que vão permitir a colateralização do direito de uso e aproveitamento da terra (DUAT) sem ferir os dispositivos legais vigentes. Também dele resulta a recomendação para a inclusão de elementos de clarificação no regulamento de terras o que tornará explícito que a colateralização do DUAT não é proibida. Para a realização deste trabalho foi feita uma revisão bibliográfica que incluiu os relatórios e declarações finais dos Foruns de Consulta sobre Terras, documentos do governo relativos à matéria de terras e estudos sobre a transmissibilidade dos títulos de uso e aproveitamento da terra. Também foi revista diversa legislação com impacto no uso e aproveitamento da terra com destaque para a Constituição da República, Lei e Regulamento de Terras, Código do Registo Predial e a legislação que cria a Central de Registo de Garantias Mobiliárias.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra

African Economic Outlook 2021: From Debt Resolution to Growth: The Road Ahead for Africa - African Development Bank (African Development Bank, 2021)
The 2021 edition of the African Economic Outlook focuses on debt resolution, governance, and growth in Africa. Chapter 1 examines Africa’s growth performance and outlook amid the COVID–19 pandemic. The chapter emphasizes policy options to mitigate the effects of the pandemic in the short, medium, and long terms. Chapter 2 explores the causes and consequences of Africa’s debt dynamics by showing how the changing structure and composition of debt create vulnerabilities. In chapter 3, the report takes stock of the challenges in the current global architecture for debt resolution and explores the link between governance and growth with an emphasis on proposed reforms to improve the processes of debt resolution, governance, and sustainable growth
Publisher: African Development Bank Group 978-9973-9854-5-3 (electronic)
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; governance / governação; health - COVID-19 / saúde – COVID-19

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Guião metodológico para gestão de terras urbanas: gestão de terras urbanas municipais - República de Moçambique: Ministério do Meio Ambiente (República de Moçambique: Minitério da Terra e Ambiente, 2020)
O objectivo deste manual é auxiliar os municípios no contexto da gestão de terra, com especial foco na regularização do DUAT (Direito de Uso e Aproveitamento da Terra) e respectivas construções. O manual pretende abranger o maior número de situações que ocorrem no dia-a-dia, apresentando soluções apoiadas na presente legislação. Pretende-se que o manual seja um valioso material de apoio à capacitação das equipas técnicas dos municípios e áreas urbanas. O objectivo do manual é igualmente informar o público e capacitar os técnicos dos municípios e outras instituições com melhores técnicas e práticas para aperfeiçoar a gestão de terras de acordo com a legislação actual.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; governance / governação; land governance / gestão de terra; urbanization / urbanização

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

A governação municipal em contextos de alternância política em Moçambique: algumas notas a partir do município de Gurué (2014-2018) - António, Bernardino (Desafios para Moçambique 2020, 2020)
O artigo discute duas questões principais. A primeira é sobre o conflito nas relações de poder entre o Governo Municipal e o Governo Distrital na questão das lideranças comunitárias dos bairros do município, onde se procura mostrar a forma como a Frelimo, através do uso do poder de tutela administrativa e financeira do Estado, restringia a governação do Movimento Democrático de Moçambique (MDM), possibilitando a existência de duas estruturas comunitárias conflituantes ao nível dos bairros. A segunda refere-se à luta pelo protagonismo político-partidário entre os dois poderes na prestação de serviços públicos, destacando a forma como afectava a prestação dos serviços de abastecimento de água e do bem-estar dos cidadãos naquela autarquia. Para analisar estas questões, o artigo desenvolve duas secções, além desta introdução. A primeira secção, que se segue, aborda as eleições e a alternância política nas autarquias em Moçambique, analisando todas as eleições, desde as primeiras, realizadas em 1998, até as eleições de 2013, e a experiência da governação nas autarquias que tiveram alternância política no passado. A segunda retrata os desafios da governação do MDM no município de Gurué. Este artigo é resultado de uma pesquisa realizada no município de Gurué em 2018, no âmbito do projecto de pesquisa Barómetro da Governação Municipal, em curso no Instituto de Estudos Sociais e Económicos (IESE). A pesquisa baseou-se numa metodologia qualitativa, com recurso a entrevistas semiestruturadas, discussões em grupos focais e observação no terreno, realizadas em 11 bairros do município de Gurué nomeadamente Contap, Escola Secundária, Barragem, Archote, 25 de Junho, Serra, Lussa A, Lussa B, Moneia, Cimento e Malessane. Foram realizadas nove discussões em grupos focais e 22 entrevistas semiestruturadas com moradores, membros do Governo Municipal (vereadores), membros da Assembleia municipal, líderes comunitários, comerciantes locais, vendedores informais, partidos políticos e funcionários do Governo Distrital de Gurué. A pesquisa de campo decorreu ao longo de 20 dias, entre Abril e Junho de 2018.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; governance / governação

Análise de Economia Política da Governação Local Moçambique - Eurosis (Mozambique Monitoring and Evaluation Mechanism and Services (MMEMS), 2020)
A governação local em Moçambique continua a desenvolver-se em duas vertentes: a desconcentração de poderes, através dos órgãos locais do Estado (secretarias de Estado da província, administrações distritais, etc), e a devolução do poder através dos órgãos de poder local (presidentes de conselhos autárquicos e governadores provinciais eleitos). O processo de criação de autarquias tem sido muito lento e a maioria dos cidadãos vive em áreas geridas pelos órgãos locais do estado e não por órgãos eleitos directamente por si. Não é ainda claro como vai funcionar a administração pública no novo figurino que criou a representação do Estado nas províncias onde existem governadores eleitos e um governo estabelecido. O que é claro, é a forte tendência para a centralização do partido político no poder e para a intervenção directa na gestão local da coisa pública, o que afecta a inclusão, transparência e prestação de contas em todas as áreas de governação. O quadro de políticas e legal é disperso e omisso em relação a como se realiza a participação dos cidadãos e cidadãs na governação em geral e como se promove a inclusão, transparência e prestação de contas. É também limitado o quadro em que operam serviços fundamentais para a transparência da administração pública, como por exemplo, os serviços de inspecção de saúde e educação, cujo quadro regulatório limita o potencial destas intervenções. Este contexto cria oportunidades para o exercício de poder discricionário a todos os níveis e leva a que intervenções fiquem dependentes do interesse político dos líderes aos vários níveis para a sua implementação. Num contexto de uma corrupção generalizada, isto é um obstáculo à realização de actividades e sustentabilidade das intervenções. Apesar das limitações apontadas, existem oportunidades e espaços para promover uma maior participação dos cidadãos e melhor prestação de contas do sector público, os quais podem ser usados como base para novas intervenções. Assim, apesar da ausência de um bom quadro legal, há alguma legislação e posições públicas do governo que remetem para um primado do cidadão, para um serviço público de qualidade e inclusivo e para o combate à corrupção. Há também mecanismos e processos que assumem a participação informada dos cidadãos nos processos de decisão sobre questões do desenvolvimento em geral (IPCC, assembleias autárquicas e provinciais) e da saúde e educação em particular (comités das unidades de serviços). Existem formalmente instituições e processos que têm como função garantir uma administração pública isenta e de qualidade (inspecção, tribunais administrativos provinciais, gabinetes anticorrupção). O nível de funcionamento destes mecanismos e processos varia muito e está dependente do interesse dos governantes locais, da mobilização comunitária e dos recursos existentes). Assim, pode dizer-se que há uma base para sobre a qual trabalhar para conseguir mais transparência, prestação de contas e inclusão ao fortalecer a governação local ao nível provincial, distrital e local (da unidades de prestação se serviços). Também o apoio à inspecção de saúde e educação pode contribuir para a melhoria da qualidade de serviços prestados aos cidadãos ao assegurar um melhor seguimento das regras e protocolos de prestação de serviços. É importante notar, contudo, que para além dos obstáculos acima referidos, o presente momento coloca desafios particulares ao desviar a atenção do governo para a resposta aos conflitos armados e à pandemia do COVID-19.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; GP - Nampula; GP - Zambézia; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; education / educação; governance / governação; health / saúde; institutions / instituições

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
978-989-8464-46-0
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Final Evaluation Report - “Improving oversight in Mozambique's governance” (2016-2019) - FCG International Ltd (FCG International Ltd, 2019)
An external evaluation of the project was conducted in April - May 2019. It looked into the strategy, performance and attainment of the general development goals. The results of the evaluation will be taken into account in the planning of a possible second phase of the project. According to the evaluation, the project is highly relevant both for the strategic partnership between Finland and Mozambique, as well as for the sustainability and inclusiveness of the economic growth arising from the extractive industries and the development of democratic governance. Finnish discretionary government transfers are used to support the Improving Oversight in Mozambique’s Governance 2016–2019 project, which aims to strengthen parliamentary oversight of the management of natural resources in Mozambique. It is a joint project of three organisations; Netherlands Institute for Multiparty Democracy (NIMD), Political Parties of Finland for Democracy (Demo Finland) and Instituto para Democracia Multipartidária from Mozambique (IMD). The project was launched in Mozambique in 2017 and it will be closed at the end of 2019; with a budget of EUR 1,500,000. The evaluation emphasises that strengthening parliamentary oversight is a long-term objective. The project has managed to reach preliminary results in a short time frame in that, for example, Members of Parliament have a better understanding of the challenges met by the extractive industries, and for the first time in Mozambique, there is regular exchange of information and cooperation between national and provincial parliaments. However, performance is not on a sustainable foundation. Sustainable impacts require that a greater number of MPs are trained and the training and research centre of Parliament and the technical secretariats of the provincial parliaments are strengthened. In addition to capacity building, the Parliament should be strengthened by creating wider partnerships and networks with other actors in society. In order to consolidate the results of the project and to improve their sustainability, the evaluation strongly recommends the Ministry for Foreign Affairs to continue the project in cooperation with the new Parliament, which will be elected in October 2019, and with provincial parliaments. It would be useful for the new MPs starting their work at the beginning of 2020 that they make use of the materials produced during the project and consult the MPs who were trained during the project. Additionally, the evaluation recommends the Ministry for Foreign Affairs to continue the project with the same partners, because they have managed to establish well-functioning and confidential relations with the Parliament and other political actors.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; decentralization / descentralização; governance / governação

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Mozambique plantation leaves no land or jobs for villagers - Adler, Nils (New Internationalist, 2018)
In northern Mozambique, villagers were promised jobs to replace land taken for forestry. Five years later, they’re still waiting, discovers Nils Adler.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Vampires, Jihadists and Structural Violence in Mozambique: Reflections on Violent Manifestations of Local Discontent and their Implications for Peacebuilding - Weimer, Bernhard (2018)
This essay seeks to explain, in a historical perspective, recent violent attacks on local institutions and representatives of the Mozambican state. Case studies are taken from three Mozambican Provinces, to which historical cases are added showing similar patterns and targets of armed attacks. Based on desk research , interviews and the review of anthropological and political economy literature, the main causes of local conflicts – all of which with their specific contexts and narratives – are identified as being threefold: Firstly, the historically entrenched political economy dominated by Frelimo deals with discontent and dissent in an authoritariina and often violent way, or, in the words of the anthropologist Bjørn Bertelsen, with ‘warfare as governance’. Secondly, the Limited Access Order firmly established in Mozambique produces socioeconomic exclusion of local social, economic and political stakeholders and interests, notably when it is linked to the extraction of natural resources. A third factor is a ‘now future’ perspective of Mozambican youth, the demographic majority. Caught in ‘waithood’ (Alcinda Honwana), it is alienated from their local communities and cultures, but not absorbed by the society and economy. This makes particlulary male youth vulnerable to global influences, and promises of peers, sometimes associated with radical religious thought and crime networks. The essay further examines the extent to which N-E part of Mozambique with its enormous investments in a Liquified Natural Gas industry is vulnerable to the influence of militant Islam. The study concludes with suggestions to address the local conflicts, emerging at a time, when the long standing ‘warfare’ between the Frelimo Government and Renamo is being negotiated towards a political settlement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Country Results Brief 2018 - Mozambique - African Development Bank (African Development Bank, 2018)
Over the last decade, Mozambique has been one of the fastest-growing African economies, enjoying average economic growth of about 8% between 2004 and 2015. It received strong support from the international community during the period (for example, in 2014 it received US$2 billion in official development assistance). In parallel, the country has embarked on major reforms — especially fiscal reforms and tax administration — and has opened up to foreign investment, particularly for the exploitation of its natural resources.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; governance / governação; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; private sector / setor privado

Barómetro Municipal 2017. Relatório de dados quantitativos. - IESE (Instituto de Estudos Sociais e Económicos (IESE), 2018)
É o novo relatório de pesquisa produzido por uma equipa de investigadores do Instituto de Estudos Sociais e Económico (IESE), coordenada por Salvador Forquilha, no quadro de um projecto de investigação em curso sobre a avaliação dos munícipes em relação ao desempenho da governação municipal em Moçambique. Este primeiro “Barómetro da Governação Municipal 2017” (BGM) explora dados quantitativos relativos à percepção dos munícipes sobre as diferentes vertentes da actuação dos órgãos e serviços municipais e que podem permitir às autoridades municipais melhor conceberem os seus planos de governação e a responderem de maneira mais eficaz às expectativas dos munícipes. Refira-se que nesta primeira fase do projecto BGM foram abrangidos oito municípios, cobrindo diferentes regiões do país, nomeadamente Beira, Ilha de Moçambique, Lichinga, Manjacaze, Nampula, Pemba, Quelimane e Tete.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; governance / governação

Afrobarometer Round 7. Summary of Results for Mozambique, 2018 - Ipsos Mozambique (Ipsos Mozambiqu, 2018)
Afrobarometer is a pan-African, non-partisan research network that conducts public attitude surveys on democracy, governance, economic conditions, and related issues in countries across Africa. Six rounds of surveys were conducted between 1999 and 2015, and Round 7 surveys are being carried out in 2016-2018. Afrobarometer conducts face-toface interviews in the language of the respondent’s choice with nationally representative samples of 1,200 or 2,400 respondents. Afrobarometer is produced collaboratively by social scientists from across Africa. Coordination is provided by the Center for Democratic Development (CDD) in Ghana, the Institute for Justice and Reconciliation (IJR) in South Africa, the Institute for Development Studies (IDS) at the University of Nairobi in Kenya, and the Institute for Empirical Research in Political Economy/School of African Economics (IERPE/ASE) in Benin. Michigan State University (MSU) and the University of Cape Town (UCT) provide technical support to the network.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Parte IV - Eleições, Governação Local e Sociedade Civil - Brito, Luís de; Chivulele, Fernanda Massarongo (Economia, Recursos Naturais, Pobreza e Política em Moçambique - Uma colectânea de textos, 2017)
IDeIAS Nº2 Uma nota sobre o recenseamento eleitoral IDeIAS Nº5 Beira – o im da Renamo? IDeIAS Nº6 Sem surpresas: abstenção continua maior força política na reserva em Moçambique … até quando? IDeIAS Nº8 Sobre os votos nulos IDeIAS Nº20 Sobre a transparência eleitoral IDeIAS Nº22 Uma análise preliminar das eleições de 2009 IDeIAS Nº48 Sobre resultados eleitorais e dinâmica eleitoral em Sofala IDeIAS Nº50 Uma relexão sobre o calendário e o recenseamento eleitoral para as eleições autárquicas de 2013 IDeIAS Nº38 Comissão Nacional de Eleições: uma reforma necessária IDeIAS Nº83 Rever o sistema eleitoral IDeIAS Nº3 Orçamento participativo: um instrumento da democracia participativa IDeIAS Nº16 A primeira reforma iscal autárquica em Moçambique IDeIAS Nº18 Relexões sobre parcerias público-privadas no inanciamento de governos locais IDeIAS Nº21 Pequenos provedores de serviços e remoção de resíduos sólidos em Maputo IDeIAS Nº41 Estado e informalidade: como evitar a “tragédia dos comuns” em Maputo? IDeIAS Nº66 Reformas de descentralização e serviços públicos agrários em Moçambique: porquê persistem os desaios? IDeIAS Nº70 Autonomização local para quê? Questões económicas no debate sobre autonomia local IDeIAS Nº24 Sociedade civil em Moçambique e no mundo IDeIAS Nº27 Sociedade civil e monitoria do orçamento público IDeIAS Nº58 As “revoltas do pão” de 2008 e 2010 na imprensa IDeIAS Nº61 Indignai-vos! IDeIAS Nº19 “O inimigo é o modelo”! Breve leitura do discurso político da Renamo IDeIAS Nº62 Media e campanhas eleitorais
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; governance / governação

As Autoridades Tradicionais nos Processos de Governação Descentralizada em Moçambique - Campos, Luciana Martins (Universidade Federal de Pernambuco, 2017)
A partir da década de 1990 iniciou-se, em vários países da África Subsaariana, um movimento de liberalização e descentralização política com a adoção de regimes democráticos. Associado a esse processo se têm em curso reformas administrativas e legislativas que visam incorporar as autoridades comunitárias e tradicionais à administração pública local a partir do reconhecimento de sua importância social e representativa para certas comunidades rurais, onde a presença do Estado se faz menor ou de modo deficitário. No entanto, esse lugar de importância social e cultural das autoridades tradicionais, em específico, só existe enquanto herança do Estado bifurcado colonial, conduzindo à elaboração de um sistema misto de governo na atualidade, onde as autoridades tradicionais seguem desempenhando funções “administrativas” semelhantes às exercidas no período colonial na lógica do indirect rule. As relações das autoridades tradicionais com o Estado em termos de administração local expõe uma situação de hibridismo institucional em decorrência do desafio de penetração do Estado enquanto administração pública e burocrática que, portanto, coabita com lógicas informais de funcionamento da administração e da realidade jurídica.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; authority / autoridade; decentralization / descentralização; governance / governação

A Economia Política da Descentralização em Moçambique: Dinâmicas, Efeitos, Desafios - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
O livro aborda a questão da descentralização mediante uma abordagem multidisciplinar e multissectorial, considerando o ângulo visual de tipo político, assim como institucional, da administração pública ou da burocracia, da economia, das finanças (públicas) e da sociedade. O objectivo que se põe tem a ver com o relacionamento entre descentralização e democracia. Trata-se de um assunto conhecido e enfrentado várias vezes no debate próprio da ciência política: será que uma maior descentralização corresponde a um nível mais avançado de democracia? Moçambique é um País ainda novo, quanto à sua vida democrática. E o livro oferece um quadro claro da história da descentralização desde 1992 até hoje; entretanto, a tese de fundo é a seguinte: a classe política que sempre esteve no poder procurou sistematicamente travar ou limitar os processos de descentralização. Será que esta tese é aceitável? Será, sobretudo, que esta tese sai comprovada das evidências que o livro traz?
OCLC: 1062395381
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Accepted: 2016-08-26T11:02:32Z
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

Socio-economic impacts of private land use investment on rural communities: Industrial forest plantations in Niassa, Mozambique - Bleyer, Maja; Kniivilä, Matleena; Horne, Paula; Sitoe, Almeida; Falcão, Mário Paulo (Land Use Policy, 2016)
East Africa has experienced an increase of private land use investments in the past years. Rural households have consequently faced crucial changes in their livelihoods. This paper explores the socio-economic impacts of industrial forest plantations on rural communities in Niassa, Mozambique. According to our results private forest plantations have the potential to positively impact local people’s wealth and well-being, if enough emphasis is given to minimizing the negative impacts. The household survey data of 218 observations from five villages were analyzed using binary and multinomial logistic regression analyses. The study shows that forest plantations have threatened the basis of traditional rural livelihoods by reducing the availability of natural resources and through the relocation of agricultural plots. However, investments have also supported the diversification of livelihood strategies in the communities by providing formal employment and by increasing business and trading activities. As growing population and traditional agricultural practices have led to the overexploitation of natural resources, non-natural resource-based livelihood strategies increase the resilience of a household. The majority of respondents reported plantations to have either no overall impact or a positive impact on the well-being of their household. According to our results, socio-economic household characteristics only marginally explain respondents’ perceptions of the impacts of forest plantations but perceptions differ significantly between individual villages.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Accountability Through Active Citizenship: Improving Petroleum Governance in Ghana, Mozambique & Tanzania - Arregui, Chiqui (Oxfam America, 2015)
The objective of the baseline survey is to analyze and document the situation around accountability, transparency and governance of the O&G sector in the country prior to the implementation of the Oxfam project. It focuses on a selected group of indicators chosen for the country program logical framework, identified and approved in the Baseline Inception Phase. A total of 33 people were interviewed in the context of this baseline. This was accompanied by a thorough national and international literature review. It was not possible to gain access to some key Government and CSO representatives at sub-national level and any of the three O&G companies contemplated in the context of this baseline, which could affect the comprehensiveness of findings. It is expected that a similar exercise be conducted at the end of the program to gauge the changes brought about by program interventions. The fieldwork for the baseline was conducted in December 2014. Baseline findings are presented in line with program outcomes, broadly focusing on building the capacities of (i) communities (Outcome 1); (ii) CSOs and the media (Outcome 2) and (iii) Other stakeholders (Outcome 3).
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; governance / governação

Guião de consulta e participação da sociedade civil e cidadãos no funcionamento dos conselhos consultivos locais - Monjane, Celso; Salimo, Padil (MASC, 2014)
O presente guião é um instrumento que tem em vista dotar as OSC e cidadãos de modo geral, de conhecimentos sobre o funcionamento dos Conselhos Consultivos Locais (CCLs) de maneira a facilitar a sua participação e a alargar as suas intervenções na área de monitoria e advocacia da governação a nível distrital. Estão apresentados neste guião, os elementos que permitem perceber a organização, a estrutura, funções, e responsabilidades dos Conselhos Consultivos Locais, como eles funcionam, as oportunidades existentes para a participação das OSC e cidadãos de um modo geral na articulação com os Conselhos Locais por forma a estimular diálogo e contribuir na melhoria da sua influência na tomada de decisões e na melhorias na prestação de serviços às comunidades a nível dos distritos pelos governos distritais. O guião está estruturado em cinco secções. A primeira secção, apresenta o contexto, objectivos e a metodologia usada na sua elaboração; a segunda secção, procura explicar os principais elementos sobre a participação e consulta comunitárias, as formas de organização das comunidades locais para a participação comunitária, e a importância da participação e consulta comunitária, bem como uma explicação sobre como a consulta e a participação é feita a nível distrital. A terceira secção, apresenta detalhadamente aspectos sobre funcionamento, tarefas e estratégias de trabalho, bem como formas de prestação de contas. A quarta secção, fala sobre os mecanismos de escolha dos membros dos Conselhos Consultivos Locais, número de membros e direitos e deveres que eles possuem. A quinta secção, fornece algumas bases sobre como a sociedade civil e cidadãos podem contribuir para o fortalecimento dos CCLs, bem como, as estratégias para incrementar mecanismos de monitoria e advocacia.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; citizenship & participation / cidadania e participação; collaboration / colaboração; governance / governação; government policy / politica governamental

Displacement and Dispossession Through Land Grabbing in Mozambique: The Limits of International and National Legal Instruments - Twomey, Hannah (Refugee Studies Centre (RSC), 2014)
This working paper examines the limitations of international and national law to address displacement and dispossession from land grabs within the case study of Mozambique. The main question that I seek to answer is: What limits international and national law in addressing displacement and dispossession due to land grabs in Mozambique? I will argue that the limits of law to address displacement and dispossession are not due to a lack of institutionalising international good governance norms into domestic-level legal frameworks. Nor can the limits be attributed to state incapacity. Rather, the limits of law lie within the norm implementation process, wherein norms are conditioned by the local Mozambican governance context to serve domestic interests
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; Law - Rule of Law / Law - Estado de Direito; governance / governação; land governance / gestão de terra

Guião de Consultas Comunitárias - Tankar, Issufo (Centro Terra Viva (CTV), 2014)
Em 2009, o Centro Terra Viva (CTV) publicou o Guião de Consultas Comunitárias, como parte do seu esforço em melhorar a aplicação da legislação sobre terras e outros recursos naturais. O guião resultou de várias pesquisas de campo realizadas pelo CTV e outras organizações que trabalham na área de Terras. No entanto, a aprovação do Decreto n° 43/2012 de 10 de Outubro, seguida do Diploma Ministerial n° 158/2011 de 15 de Junho, uma parte significativa do Guião ficou ultrapassada. Por outro lado, foram aprovadas directrizes pelo Fórum de Consulta sobre a Terra que são relacionadas a este tema. Deste modo, e como forma de facilitar a interpretação e aplicação do quadro legal sobre consultas comunitárias, o Centro Terra Viva, produziu este guião de consultas comunitárias destinado às comunidades, técnicos do Estado, técnicos de ONG’s e todos actores que trabalham na área de Terras.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Mozambique land policy development case study - Locke, Anna (Overseas Development Institute, 2014)
This case study has been produced in response to a request made to the Evidence on Demand Helpdesk. The objective of the request was to provide a detailed case study on the evolution of land policy in Mozambique and provide the reader with insights into what is viewed as one of Africa’s most progressive land laws, recognising multiple forms of tenure. Mozambique has experienced accelerated rates of growth over the past decade, averaging 7.2% per year, with projected growth rates of over 8%. However, this high growth rate has failed to translate into significant reductions in poverty and inequality has increased in almost all parts of the country. While growth has been driven by capital-intensive projects, mainly in the extractives sector, agriculture is seen as an important foundation for economic development and there has been a high level of interest in acquiring large tracts of land for investment over the past six years. Mozambique is one the most land-abundant countries in Africa, with around 80 million hectares (has). Currently, only five million hectares are cultivated, mainly by smallholders under rain-fed, traditional systems, and only 3-5% of landholdings are formally registered.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra

Perfil Do Distrito De Pemba Metuge Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Pemba Metuge; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação; poverty / pobreza

Orientacoes superiores: Time and bureaucratic authority in Mozambique - Gonçalves, Euclides (African Affairs, 2013)
This article examines the production, circulation, and interpretation of regulatory documents in contemporary Mozambique in order to highlight their central importance to processes of governance. The empirical focus is on orientações superiores – written and oral documents issued by ﬁgures and institutions of authority with the intention of advising on procedures for policy formulation and implementation. By producing orientações superiores in a way that leaves their intent ambiguous and their status provisional, party and state ofﬁcials shift the focus of policy making from substance to process. In this way, bureaucratic authority is produced and reinforced through the manipulation of the timing of policy implementation. This perspective expands current understandings of African governance that on the whole have been limited to the analysis of the effectiveness of African institutions and policies, leaving the tactical effects of ambiguity, timing, and provisionality in policy implementation undertheorized.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - ethnography / etnografia; authority / autoridade

Facing the forest entrepreneurs - Healy, Hazel (New Internationalist, 2013)
Communities are scrambling to protect their lands from the tree plantations multiplying across Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra

‘Operation of the Market's Study. How the poor access, hold and trade land: Findings from research in two settlements in Tete, Mozambique - Gordon, Ross; Taljaard, Reathe; Massuanganhe, Egildo, Egildo (Progressus Research Development Consultancy, 2013)
The way in which informal land transactions occur and the extent to which they result in tenure security and asset creation in these informal settlements is not well understood. For this reason this study comprises research into two informal settlements (namely Matundo and Mateus Sansão Muthemba [Sansão Muthemba]) in Tete, Mozambique, so as to understand how the poor access, hold and trade land. This research forms part of a larger research programme being undertaken by Urban LandMark which includes similar studies in Lilongwe (Malawi), Maputo (Mozambique), Luanda (Angola) and Durban, Cape Town and Johannesburg (South Africa). Reports on these other research projects can be seen on www.urbanlandmark.co.za.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; governance / governação; land governance / gestão de terra

Reality checks in Mozambique. 2nd Annual Report - Governance - Tvedten, Inge (ORGUT Consulting AB, 2012)
The Reality Checks are implemented between 2011- 2016, with fieldwork being carried out each year in the Districts of Cuamba, Majune and Lago in the Niassa Province. Sub-Team Leaders are Carmeliza Rosário, Minna Tuominen and Inge Tvedten. This is the Annual Report for the 2nd Reality Check, synthesising the main findings from the three sub- reports. The report is written by the Team Leader for the Reality Checks in Mozambique Dr. Inge Tvedten - with support from Carmeliza Rosário, Minna Tuominen and Aslak Orre (Thematic Advisor).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; governance / governação; poverty / pobreza

Afrobarometer Round 5. Summary of Results for Mozambique, 2012 - Centro de Pesquisas de Governação e Desenvolvimento (CPGD) (Centro de Pesquisas de Governação e Desenvolvimento (CPGD), 2012)
The Afrobarometer is a comparative series of public attitude surveys that will be covering up to 35 African countries in Round 5 (2011-2013). Based on representative national samples, the surveys assess citizen attitudes to democracy and governance, markets, and civil society, among other topics. The first round of surveys was conducted between 1999-2001 and covered seven Southern African countries (Botswana, Lesotho, Malawi, Namibia, South Africa, Zambia and Zimbabwe), three countries in West Africa (Ghana, Nigeria and Mali) and two in East Africa (Uganda and Tanzania). Round 2 surveys were completed by November 2003 with four new countries added: Kenya, Senegal, Cape Verde and Mozambique. Round 3 surveys were conducted from March 2005 to February 2006 in the same countries, plus Benin and Madagascar. The 4th Round of surveys covered 20 countries between 2008 and 2009, with the addition of Burkina Faso and Liberia.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Country Review Report: Republic of Mozambique - African Peer Review Mechanism (African Peer Review Mechanism, 2009)
The report is divided into seven chapters. This introductory chapter is followed by Chapter Two, which provides an overview of Mozambique as a backdrop to the report. Chapters Three to Six evaluate developments and challenges in the four APRM focus areas (Democracy and Political Governance; Economic Governance and Management; Corporate Governance; and Socio-Economic Development) respectively. Each of these chapters has two sections: the first analyses the codes and standards of the APRM, while the second assesses the APRM‘s objectives for that thematic area. Each section begins with a summary of the CSAR, followed by the findings of the CRM and, finally, the APR Panel‘s recommendations on the identified challenges. Effort has also been made to highlight areas of best practice in boxes. Chapter Seven discusses the cross-cutting issues considered critical due to their wider impact on governance and thus require holistic, immediate and urgent attention. These salient issues are the following: Poverty and Inequality; Party/government/business dichotomy; Land; High levels of illiteracy; Eliminating aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. The Chapter also highlights three special issues of interest to Mozambique and the Mission - the Environment, land mines and Beira city. The NPOA received from Mozambique and the comments of the government are annexed to the report, as mandated by the APRM rules.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; governance / governação

Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
ISBN 978-91-85735-17-4
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Mozambique - Lloyd, Robert B. (Countries at the Crossroads 2007: A Survey of Democratic Governance, 2007)
Countries at the Crossroads is an annual survey of government performance in 30 key countries worldwide that are at a critical crossroads in determining their political future. Crossroads provides a unique comparative tool for assessing government performance in the areas of accountability and public voice, civil liberties, rule of law, and anticorruption and transparency. The countries evaluated in Crossroads represent a range of governments: traditional or constitutional monarchies, one-party states or outright dictatorships, failed states, states where reforms have stalled or lagged behind, and states that suffer from insurgencies. The survey provides a comparative, in-depth assessment of democratic governance intended to help government officials, scholars, educators, nongovernmental organizations, and the media identify areas of progress and highlight points of concern. For the international community, the survey helps target diplomatic efforts and reform assistance. The narratives and scores clearly highlight the problems and successes of each government, and separate recommendations sections prioritize the steps that should be taken by the countries in question to remedy deficiencies in governance.
Keywords: G - Mozambique / Moçambique; L - english / inglês; governance / governação

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude

State Recognition and Democratization in Sub-Saharan Africa: A New Dawn for Chiefs? - Buur, Lars; Kyed, Helene Maria (Palgrave Macmillan, 2007)
State Recognition and Democractization in Sub-Saharan Africaآ explores the link between liberal-style democratization and state recognition of traditional authority in Sub-Saharan Africa. Being critical and empirically grounded, the book explores the complex, often counter-balancing consequences of the involvement of traditional authority in the wave of democratization and liberal-style state-building that has rolled over sub-Saharan Africa in the past decade. It scrutinizes how, in practice, traditional leaders are being drawn into governance in Mozambique, Zambia, Namibia, Malawi, Burkina Faso, and the Somali region of Ethiopia, and relates these developments to state governance in the declining democracy of Zimbabwe and the emerging state of Northern Somalia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; authority / autoridade; decentralization / descentralização; governance / governação

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

From ‘Abaixo’ to ‘chiefs of production’: Agrarian change in Nampula province, mozambique, 1975–87 - Dinerman, Alice (The Journal of Peasant Studies, 2001)
This article reconstructs key aspects of the evolving relationship between state institutions and former regulos (Portuguese‐appointed chiefs), in Nampula Province, Mozambique during the first 12 years of independence. In doing so, it simultaneously draws on and critiques two opposing interpretations of revolution and counterrevolution which have dominated scholarly production on post‐independence Mozambique and have polarized Mozambican studies in recent years. Against both sets of literature, my study finds that state socialism did not always and everywhere bring major disruptions to grassroots structures of authority; rather, many families who had been recognized by the Portuguese as royals were able, through a variety of strategies, to maintain their grip on local power. Secondly, I argue that the provincial government's enlistment of former regulos to serve as ‘chiefs of production’ was but one aspect of an attempt on the part of officialdom to recreate the most salient aspects of the colonial cotton regime rather than a war‐induced genuflection by the Frelimo regime to Renamo on the question of chiefly rule, as has been claimed by what I call ‘revisionist’ scholarship. Frelimo's refusal to acknowledge the role of villagization in agricultural decline throughout the country, a point raised and highlighted by revisionist writing is, however, crucial to understanding the ideological practices that helped justify and legitimate the return to Portuguese precedent on matters relating to rural labour. The reasons why Nampula was the site of these initiatives are explored.
Publisher: Routledge _eprint: https://doi.org/10.1080/03066150108438766
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; agriculture / agricultura; authority / autoridade